IMPACT OF INTERACTION AMONG TEACHERS AND STUDENTS FOR ACADEMIC PERFORMANCE: A CASE STUDY AT FACULTY OF EDUCATION, UNIVERSITY OF SINDH, PAKISTAN - Baqir Ali; Dr. Sumera Irum; Rehman Ali; Riaz Ahmed Chana; Samina Khanzada (International Journal of Contemporary Issues in Social Sciences, 2024)
Students’ affiliation with teachers, they spent 5 to 7 hours in day and 10 months with their teacher in departments. This study ascertained impact of interaction among them for academic performance. Interaction known as motivational tool for students, that they accomplished their studies. Tutoring diffused rapidly around the world. Universities improved their standard through quality of education and students’ educational performance through educational quality. It examined challenges for interaction among teachers and students that they ensured students success. Research done at “faculty of Education Hyderabad, University of Sindh Jamshoro, Pakistan”; as a case study”. Researcher examined effect of teachers’ interaction on students. The random sampling method applied for data gathering from different departments. Descriptive applied through analysis mean and standard deviation to find teachers effect of communication on students education and their educational success. The results displayed constructive affiliation among both (teachers and students). It was somehow difficult to create constructive affiliation amongst both, when they reached to the certain period. They became mature. These affiliations created learning experience of students. This research paper, however, displayed that there was fair rapport among teachers and students educational performance that created friendliness environment for the students success.